"It was like a little community": An ethnographic study of online learning and its implications for MOOCs. Issue 1 (September 2013) - WASSON, CHRISTINA
Abstract : In this time of social, technical, educational and industrial upheaval, time and space are being compressed and stretched as social actors develop new practices in response to shifts in their lived experience. In the American educational sector, these phenomena have crystalized in the meteoritic rise of MOOCs, massive open online courses. The story of their ascent weaves together neoliberal shifts in financing education, technology developments, and perceived business opportunities. MOOCs have captured the imagination of the business press, venture capitalists, and university leaders. However, surprisingly little attention has been paid to the perceptions of students who are taking online courses – in other words, the users. Drawing on an ethnographic study of a small online class, this paper describes the limitations of MOOC pedagogies by comparison with low‐enrollment online courses, and concludes by casting doubt on the effectiveness of MOOC learning experiences as well as MOOC business models.